Rationing Capacity in Advance Selling to Signal Quality - Yu, Man; Ahn, Hyun-Soo; Kapuscinski, Roman (Management Science, 2015)
We consider a seller who can sell her product over two periods, advance and spot. The seller has private information about the product quality, which is unknown to customers in advance and publicly revealed in spot. The question we consider is whether the seller has an incentive to signal quality in advance and, if so, how she can convey a credible signal of product quality. We characterize the seller's signaling strategy and find that rationing of capacity in the advance period is an effective tool of signaling product quality. We find that the high-quality seller can distinguish herself by allocating less capacity than the low-quality seller in the advance period. We show that this signaling mechanism exists whenever advance selling would be optimal for both the high-quality and low-quality sellers if quality were known by the consumers. Interestingly, the seller's ability to ration (rationing flexibility) sometimes disadvantages the seller; this effect is independent of product quality. This paper was accepted by Yossi Aviv, operations management.